ON THE PROTECTION OF THE RIGHTS PROVIDED BY THE CONVENTION ON THE PROTECTION OF HUMAN RIGHTS AND FUNDAMENTAL FREEDOMS IN CRIMINAL JUDICIAL - Коломієць, Наталія Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Goal: the purpose of this article is to provide insight into the current state of protection of the rights of persons sentenced to imprisonment in Ukraine; analyze the fundamental rights of convicted persons as defined by the Convention for the Protection of Human Rights and Fundamental Freedoms; highlight the legal and regulatory framework for the protection of the convicted persons’ rights at the national and international levels. Methods: general and specific scientific (special) methods were used to achieve the research goal. Results: improvement of national legislation that would protect the rights and freedoms, as well as continue the course of Ukraine on European standardization of laws. Discussion: the author finds out whether it is expedient to apply conditional release to persons sentenced to life imprisonment. The author analyzes the judgment of the European Court of Human Rights and outlines the main rights that are most often raised in criminal proceedings. Proper safeguarding and protection of the rights of both citizens and convicted persons prior to imprisonment in Ukraine require their clear legal regulation, which makes it necessary to perform a scientific analysis of the protection of the convicted persons’ rights. It is worth noting that increasing the attention to the issues of respect and protection of the rights and freedoms of persons sentenced to imprisonment today is one of the priority tasks in the field of the Criminal and Executive Law in Ukraine. The purpose of this article is to provide insight into the current state of protection of the rights of persons sentenced to imprisonment in Ukraine; analyze the fundamental rights of convicted persons as defined by the Convention for the Protection of Human Rights and Fundamental Freedoms; determine the grounds for applying to the European Court of Human Rights; highlight the legal and regulatory framework for the protection of the convicted persons’ rights at the national and international levels. Ukraine has a significant amount of regulatory legal acts intended for protection of the human rights. Some of these documents are international standards in the field of the human rights and the other part relates to the regulatory acts of the national legislation. Being based on the constitutional provisions the Criminal and Executive Code of Ukraine defines the basis for the legal status of convicted persons thus establishing their basic rights and obligations. Most of them align with the provisions of the international instruments concerning the legal status of the convictedpersons, in particular, regarding the treatment of a convicted person with respect to his human dignity; provision of the conditions for the convicted persons in compliance with the accepted standards.